Mackenna's Gold - J Lee Thompson; Sparv, Camilla; Julie Newmar; Keenan Wynn; Omar Sharif; Telly Savalas; Gregory Peck (USA Columbia Pictures Corporation, 1969)
The gangster Colorado kidnaps Marshal McKenna. He believes that McKenna has seen a map which leads to a rich vein of gold in the mountains and forces him to show him the way. But they're not the only ones who're after the gold; soon they meet a group of "honorable" citizens and the cavalry crosses their way too - and that is even before they enter Indian territory.
The gangster Colorado kidnaps Marshal McKenna. He believes that McKenna has seen a map which leads to...
Heck Allen
Languages: English, Italian, Spanish, German, French
Subtitles: English, French, Italian, Deutsch, Spanish, Nederlands, Arabic, Bulgarian, Czech, Dansk, Suomi, Hindi, Magyar, Islenka, Norsk, Polish, Portuguese, Svenska, Turkish
Keywords: Western